2020
DOI: 10.1021/acsanm.0c00846
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Grown by Galvanic Replacement on Graphene-Coated Aluminum Panels as Large-Area Substrates for Surface-Enhanced Raman Scattering

Abstract: Galvanic replacement (GR) is a widely used method to obtain substrates with nanostructure morphologies. However, there are substantial challenges related to the uniformity of the deposited nanostructures, the preparation of large-area nanocomposites, and the alteration of the morphologies deposited on substrates. Graphene was introduced into the surface of the aluminum panels in this study prior to conducting the GR reaction to incorporate graphene advantages of extremely high electrical conductivity and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Graphene-Based Nanomaterials . As with TMDs, nucleation can also be promoted to occur on pristine graphene, , but defect sites are most effective at promoting metal nanoparticle nucleation. Among the different possible defects that may exist in graphene (single-carbon vacancies, multiple-grouped vacancies, impurities, foreign atoms substitution, etc .…”
Section: From Colloidal Synthesis To In Situ Growthmentioning
confidence: 99%
“…Graphene-Based Nanomaterials . As with TMDs, nucleation can also be promoted to occur on pristine graphene, , but defect sites are most effective at promoting metal nanoparticle nucleation. Among the different possible defects that may exist in graphene (single-carbon vacancies, multiple-grouped vacancies, impurities, foreign atoms substitution, etc .…”
Section: From Colloidal Synthesis To In Situ Growthmentioning
confidence: 99%
“…Such a reshaping effect from DMSO on Au and Ag particles has been reported by other researchers too. 33,34 It has been demonstrated that DMSO binds gold atoms in a preferential way. 35 For instance, it has been reported that both O and S from DMSO could coordinate with the surface of Au nanocrystals, which stabilizes Au {311} facets and creates Au NPs in the trapezohedral shape.…”
Section: Effect Of Dmso On the Au Np/cnt Sheetmentioning
confidence: 99%
“…GD reaction is an electrochemical process that involves the redox reaction to reduce metal ions to metallic nanoparticles on the interface of substrate at ambient temperature without reducing agent. [42][43][44][45][46][47][48][49][50][51][52][53] Typically, the entire GD reaction includes an oxidation reaction (anodic electrode, Si + 6F − → SiF 6 2− + 4e − ) and a reduction reaction (cathodic electrode, Ag…”
Section: Controllable Synthesis Of Silicon-based Nanohybridsmentioning
confidence: 99%
“…GD reaction is an electrochemical process that involves the redox reaction to reduce metal ions to metallic nanoparticles on the interface of substrate at ambient temperature without reducing agent. [ 42‐53 ] Typically, the entire GD reaction includes an oxidation reaction (anodic electrode, Si + 6F − → SiF 6 2− + 4e − ) and a reduction reaction (cathodic electrode, Ag + + e − → Ag 0 or Au + + e − → Au 0 ) (Figure 3a). In particular, metallic ion is reduced on the silicon wafer surface to form metallic nanoparticles when the redox potentials of metallic ion ( e.g ., Ag + /Ag = 0.799 V) are much higher than that of silicon oxide layer ( e.g ., SiF 6 2− /Si = −1.2 V).…”
Section: Controllable Synthesis Of Silicon‐based Nanohybridsmentioning
confidence: 99%